Method and system for fatal wastewater treatment - CHANG, YUNG; CHEN, BO-SHIN; YEN, HSUANG; CHEN, CHIN-I; CHEN, MEI-YEN (2016)
The present invention discloses a method and system for wastewater treatment, including the following the steps below. A heat pump circulation system sets into wastewater collector, and then an external driving heat source is used to provide initial energy to diluted wastewater to product water vapor. Therefore, the heat pump circulation system is used to recycle the enthalpy, which comes from enthalpy of vaporization of water vapor transforming to distilled water, then the enthalpy give a heat exchanging to diluted wastewater for producing water vapor continually and a distilled water driving-equipment is used to lead out the distilled water form wastewater collector. A solidification-equipment is used to occur solidification process when a high concentration wastewater is formed. The solid, which have fatal pollutants, has less volume and can store in the safe place which never release to the environment.